PERSEBARAN POHON DIPTEROCARPACEAE DI SEPANJANG JALUR UTAMA PATROLI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PROVINSI RIAU - Ana Pratiwi; Yossi Oktorini; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Dipterocarpaceae is one of the iconic trees in Riau. Dipterocarpaceae grows in lowland tropical rain forests. Taken example, one of the lowland tropical rain forests in Riau is Taman Hutan Raya (Tahura) Sultan Syarif Hasyim. There are so many trees which belong to Dipterocarpaceae along the main patrol line of Tahura Sultan Syarif Hasyim. The Dipterocarpaceae trees along the main patrol line need to be maintained and preserved. The management of Dipterocarpaceae trees requires a distribution data of Dipterocarpaceae trees. Using the analaysis of Morisita index as a form of Dipterocarpaceae trees distribution along the Tahura Sultan Syarif Hasyim’s main patrol line formed a clustered pattern with values >1 for the right side of the line 5,35 and 3,12 for the left side of the line. Keywords:  Distribution pattern, Trees, Dipterocarpaceae, The main line patrol, Tahura